HEAVY METAL ANALYSIS OF BLEPHARIS MADERASPATENSIS (L.) HEYNE EX ROTH - S, Vijayalakshmi; Kg, Kripa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the study was to execute systematic heavy metal assessment of the plant to ensure its safe usage in herbal medicine or as nutraceuticals. Blepharis maderaspatensis (L.)Heyne ex Roth commonly called as Nethiramooli in Tamil is a widely distributed medicinal herb with a long history of traditional usage in the treatment of many ailments. Method: The plant material was collected from Thanjavur, Tamil Nadu, India, duly authenticated and heavy metal content investigated by inductively coupled plasma optical emission spectrometry. Results: Results indicated that the toxic metal, mercury was not detectable even in traces; other metals such as cadmium, chromium, molybdenum, manganese, nickel, and lead were found at very low quantities while trace elements such as iron, zinc, copper, and cobalt in fairly significant concentrations. Conclusions: These results thus substantiate the safe usage of this plant and may be used to set new standards for prescribing the dosage of the herbal drugs prepared from it, ensuring a better understanding of the risks associated with its usage.